Transvaginal NOTES cholecystectomy in my partner? No way! - Jarek Kobiela; Tomasz Stefaniak; Sebastian Dobrowolski; Wojciech Makarewicz; Andrzej J. Łachiński; Zbigniew Śledziński (Videosurgery and Other Miniinvasive Techniques)
Introduction: Natural orifice transluminal endoscopic surgery (NOTES) transvaginal cholecystectomy is being intensivelystudied. A few studies have been recently published evaluating patients’ attitude towards NOTES with its individualaccesses. However, the choice of a transvaginal access with its potential influence on sex life and fertility is notrestricted entirely to women. The sexual partner would at least give his opinion or decide together with the woman. Aim: The aim of the study was to assess the attitude of male sexual partners of potential NOTES transvaginal patientstowards the surgical access. Material and methods: Hundred males were asked for their opinion in a specially designed instrument. Results: The general attitude of male sexual partners of potential NOTES transvaginal cholecystectomy patients isnegative. With several possible problems and complications feared by the partners, they would mostly oppose or dissuadeagainst NOTES transvaginal cholecystectomy. The cosmetic benefit seems not to justify undergoing a noveltyprocedure with potential complications threatening sexual life and procreation. This attitude was especially observedin young, sexually active males with high appreciation of sexual life. Conclusions: Both scientific and educational efforts are required to prove safety and efficiency of NOTES transvaginalcholecystectomy beyond question.